Perancangan Dan Pengembangan Konten Vıdeo Promosı Dı Instagram Pada Umkm Tempat Makan Lo Ka Cıong Cıa Tang - Jimmy Pratama; Jacky Jacky (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
In today’s society, along with the development of technology and knowledge, there are many ways that can be used to promote a business. One way to promote a business that is currently on the trend is promotional media content through the Instagram application, which is also known as Instagram ads. Instagram ads are posts or Stories that a business buys to promote to users’ Instagram feeds. They can seem just like regular Instagram posts but are always marked by a “Sponsored” badge. With a potential audience of more than 928 million people, Instagram ads are a key tool for any social media marketer to market their business. The purpose of this research paper is to design promotional media content on Instagram at the MSME restaurant